Isolation of Lactic Acid Bacteria from Cabbage and Their Potensial Inhibition to Pathogenic Bacteria (Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, dan Salmonella thypimurium) - Purwohadisantoso, Kristian; Zubaidah, Elok; Saparianti, Ella (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Today, the growth of food industries has encouraged significant role of lactic acid bacteria for food processing such as for producing antibacterial agent. Cabbage is one of lactic acid bacteria sources. However, the pathogenic bacterial inhibition capability of lactic acid bacteria isolated from cabbage is still unknown. Also its ability to produce bacteriocin has not been elucidated. This research is aimed to isolate and to confirm lactic acid bacteria from cabbage, as well as to study their ability to inhibit certain pathogenic bacteria. The results showed that there were 8 lactic acid bacteria isolates wuth characteristics as follow: the morphology was round, white color, and classified as positive gram bacteria, negative catalase test, not capable to produce gas. They were supposed as homofermentatitive lactic acid bacteria. All of isolates could inhibit the growth of Staphylococcus aureus, Eschericia coli, Listeria monocytogenes, and Salmonella typhimurium. K512 isolate had the highest capability to inhibit the growth of Eschericia coli (inhibition diameter of 11.53 mm) and Salmonella typhimurium (inhibition diameter of 11.60 mm). K45 isolate had the highest ability to inhibit the growth of Staphylococcus aureus (inhibition diameter of 10.53 mm). K41 isolate had the growth inhibition capability to Listeria monocytogenes (inhibition diameter of 11.67 mm). Bacteriocin producing test showed that all of the isolates had no growth inhibition to four tested pathogenic bacteria.Keywords: isolation, lactic acid bacteria, antimicrobial activity, bacteriocin